The Nature of Christianity in Northern Tanzania Environmental and Social Change 1890-1916. - Munson, Robert B., 1967- (Lanham : Lexington Books, 2013)
The Nature of Christianity in Northern Tanzania explores the relationship between the environment and social change on Mt Kilimanjaro and Mt Meru during the German colonial period (1890-1916). The work analyzes the synergy between landscape change, exotic plant introduction, and Christian missionizing, showing how these three types of transformation impacted upon each other as well as the changing African societies to create a new African/German landscape.
Glossary 1: Words in African LanguagesGlossary 2: Words in German; Bibliography; Index; About the Author.
Print version record.
Keywords: Cultural landscapes -- Tanzania; Landscape changes -- Tanzania; Plant introduction -- Tanzania; Plants, Cultivated -- Tanzania; Social change -- Tanzania; Kilimanjaro Region (Tanzania) -- History; Meru, Mount (Tanzania) -- History; Tanzania -- History -- 1890-1918.; Germans -- Tanzania -- History; Missions, German -- Tanzania; Cultural landscapes -- Tanzania; Germans -- Tanzania -- History; Kilimanjaro, Mount, Region (Tanzania) -- History; Landscape changes -- Tanzania; Meru, Mount, Region (Tanzania) -- History; Missions, German -- Tanzania; Plant introduction -- Tanzania; Plants, Cultivated -- Tanzania; Social change -- Tanzania; Tanzania -- History -- 1890-1918.; SOCIAL SCIENCE -- Human Geography; RELIGION -- Christian Ministry -- Missions; Cultural landscapes; Germans; Landscape changes; Missions, German; Plant introduction; Plants, Cultivated; Social change; Tanzania; Tanzania -- Kilimanjaro Region; Tanzania -- Mount Meru; 1890 - 1918; Electronic books; History; Electronic books